A comparative clinical study of intrathecal hyperbaric bupivacaine with and without fentanyl for hysterectomy - Poudel, Hari; Bawa, Surinder Nath; Sharma, Surendra Mohan (Asian Journal of Medical Sciences, 2020)
Background: Spinal anaesthesia has been widely used for lower abdominal surgeries like hysterectomy.Hyperbaric bupivacaine is the most extensively used local anesthetic. Addition of fentanyl can allow the reduction in the dose of bupivacaine, increase the height and duration of sensory blockade, and reduces complications of spinal anesthesia. Aims and Objective: The aim of the study was to examine whether adding fentanyl to hyperbaric bupivacaine would increase the height of sensory blockade, accelerate the onset of sensory blockade and increase the duration of the sensory blockade. Material and Methods: This study was done in Manipal Teaching Hospital, Pokhara, Nepal that included hundred patients who underwent total abdominal hysterectomy. The patients were randomly allocated in two groups; Group I: received 0.5% hyperbaric bupivacaine 2.5 ml (12.5 mg) plus normal saline 0.5 ml. Group II: received 0.5% hyperbaric bupivacaine 2.5 ml (12.5 mg) plus 0.5 ml fentanyl (25 μg). Hemodynamic variables, onset of motor and sensory blockade, duration of sensory and motor blockade and any side effects were observed and recorded. Results: The highest and lowest sensory block in Group I was T-7 and T-9 whereas in Group II was T-5 and T-9 respectively. In group I, the mean onset till maximum height of sensory blockade was 7.04 min whereas in group II it was 5.96 min (P<0.00).There was no significant statistical difference in the incidence of side effects in both the groups. Conclusion: Intrathecal fentanyl with hyperbaric bupivacaine for spinal anesthesia significantly accelerated the onset of sensory blockade and increased its maximum height and duration.